2014
DOI: 10.1186/s40425-014-0028-y
|View full text |Cite
|
Sign up to set email alerts
|

Common gamma chain (γc) cytokines differentially potentiate TNFR family signaling in antigen-activated CD8+ T cells

Abstract: BackgroundSeveral members of the common gamma chain (gc) cytokine family are already approved (IL-2) or actively being developed as vaccine adjuvants and cancer immunotherapies. Studies have indicated that co-administration of gc cytokines may enhance the efficacy of immunotherapies that function via direct activation of co-stimulatory T cell receptors. To define the specific influence of gc cytokines on the co-stimulatory capacity of CD8+ T cells and identify combinations with synergistic potential, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 70 publications
(61 reference statements)
0
6
1
Order By: Relevance
“…Additionally, in effector CD8 + T cells, IL-6 is a master regulator of IL-21. Quite different from the results of a previous nding that incorporating a truncated IL-2 receptor β chain to a CAR induced IL-21 signaling 37 , incorporating γc in our study reduced IL-21 level as well as its downstream targets, IL-18R1, IL18RBP, and IL18RAP. The response timing of activated CD8 + T cells to the γc cytokines is critical considering the study by Hinrichs and colleagues who showed that when exogenous IL-21 was added to the culture media during antigen priming, acquisition of effector functions and induction of granzyme B were inhibited, whereas exogenous IL-2 and IL-15 had an opposite effect.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, in effector CD8 + T cells, IL-6 is a master regulator of IL-21. Quite different from the results of a previous nding that incorporating a truncated IL-2 receptor β chain to a CAR induced IL-21 signaling 37 , incorporating γc in our study reduced IL-21 level as well as its downstream targets, IL-18R1, IL18RBP, and IL18RAP. The response timing of activated CD8 + T cells to the γc cytokines is critical considering the study by Hinrichs and colleagues who showed that when exogenous IL-21 was added to the culture media during antigen priming, acquisition of effector functions and induction of granzyme B were inhibited, whereas exogenous IL-2 and IL-15 had an opposite effect.…”
Section: Discussioncontrasting
confidence: 99%
“…An increase in STAT5 phosphorylation confirmed activation of the IL-2 pathway in CD4 + effector TILs in both untreated and αCTLA-4-treated tumors in comparison to CD4 + T cells in the LN ( Figure 4 D). Further analysis of T cell activation markers revealed increased expression of CD69, CD44, GITR (Glucocorticoid-Induced TNFR-Related Protein) and CD38 upon αCTLA-4 treatment, of which only GITR ( McNamara et al, 2014 ) was decreased by IL-2 deprivation relative to controls. PD-1 expression was consistently increased and the negative co-stimulatory molecule CD101 decreased ( Schey et al., 2016 ) in all αCTLA-4 treated groups regardless of IL-2 presence ( Figures 4 E and S4 D).…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with an agonist aOX40 mAb directly stimulated CD4 and CD8 T cells and induced their expansion, differentiation, and up-regulation of prosurvival molecules (7)(8)(9)(10)(11)(12). Moreover, OX40 ligation promoted the generation of long-lived memory CD8 T cells and enhanced their function.…”
mentioning
confidence: 99%